Review: Potency of Borneo Endemic and Typical Plants as Anti-Cancer Medicines - Alhawaris Alhawaris (Jurnal Kesehatan Pasak Bumi Kalimantan, 2022)
The Island of Borneo (also known as Kalimantan), Indonesia has extensive forests overgrown with various plants. Some of them have been believed for generations and empirically have efficacy as traditional medicines. It is estimated that more than 200 medicinal plants are growing in the forests of Borneo Island. Some of them had been studied to have a number of secondary metabolites that act as anticancer, such as Bawang Dayak/Bawang Tiwai (Dayak/Tiwai Onion), Tahongai, Tanaman Sarang Semut (Ant Nest Plant), Batang Kuning (Yellow Stem)/Akar Kuning (Yellow Root), and Pasak Bumi/Tongkat Ali. Meanwhile, some of them still need to be investigated further regarding the secondary metabolites of their plant parts and their properties as herbal medicines, especially as anti-cancer, such as Sengkubak, Kayu Bajakah (Bajakah Wood), and Jahe Balikpapan (Balikpapan Ginger).Keyword: Anti-Cancer, Secondary Metabolites, Herbal Medicines, Borneo Endemic Plants